Digital human experience models for augmented reality mobile wellness devices. (28th January 2015) - Ihamäki, Pirita
Mobile wellness devices are popular in personal devices, which are used to maintain health during physical activities. This paper presents theoretical work on digital human experience models. The paper uses digital human experience models to improve the experiences that users have when they interact with mobile augmented reality devices. This paper uses user–centred design methods and results from previous studies to create digital human experience models, which can be used to capture, store, process and transmit information for mobile augmented reality wellness devices. The results showed that users can use the new augmented reality wellness devices more easily to store, process and transmit wellness information and to more easily manage their everyday lives. This paper creates the conceptual design of the digital human experience models, with experimental subjects. Future studies will create and test the complete digital human experience models (in software), with lead users.